Social frames promoting sharing in Norwegian Recovery Colleges: an ethnographic study - Sjursæther, Therese Ersvær; Øye, Christine; Mellingen, Sonja (Frontiers in Psychiatry, 2025)
IntroductionRecovery Colleges (RCs) for people with substance use and mental health challenges represent an innovation in mental health services, emphasising co-creation and adult learning. Students and course facilitators with diverse experiences engage in collaborative learning in these settings by sharing experiences, knowledge, and skills. This paper examines the social frameworks that facilitate or hinder sharing within RCs.MethodsWe conducted an ethnographic study in two distinct RC settings, using participatory observation and semi-structured interviews with facilitators, students, and leaders. We employed Goffman’s frame analysis to understand the social framework in RC and how its organisational structures and physical premises influence sharing among students and facilitators.ResultsOur results reveal layers of social frameworks that emphasise learning, recovery, strengths, equality, and open discussions about mental health. Organisational structures and physical premises significantly support or hinder these social frameworks. Clear communication, preparatory conversations, respect for boundaries, and neutral settings were identified as key aspects promoting sharing. Conversely, focus on diagnoses, top-down attitudes, inadequate preparations, excessive facilitator involvement, health-related settings, and overly exposed arrangements could inhibit sharing.DiscussionThe organic interactions within RC courses create complexities in understanding the promoters and inhibitors of sharing within these social frameworks. What promotes sharing in one setting can inhibit sharing in another. We illustrated situations where disruptions to the frames either promoted active participation for some or inhibited sharing for those who felt overwhelmed. Recognising this complexity is crucial for facilitators in RCs to effectively frame sharing and achieve mutual learning among students.